Determinants of green purchasing among electrical & electronics companies in Malaysia / Fatin Firzana Anwar and Siti Nurliyana Nabilah Che Rozela - Anwar, Fatin Firzana; Che Rozela, Siti Nurliyana Nabilah (Faculty of Business Management, 2016)
To date, the deteriorating environment has become a great concern for governments, societies, as well as business organizations all over the world. In addition, businesses are being seen as the biggest contributors to the deterioration of the environment. Hence companies and organizations are beginning to take into consideration the environment and the impact it would cause stemming from their business activities. As such, more companies are adopting sustainable management in their business operations with green purchasing being one of the methods. Malaysia has long depended on the electrical and electronics (E&E) industry as the biggest contributor to the country’s GDP in international trade. Thus this research aims to study the adoption of green purchasing practice among companies in the E&E industry in particular. The drivers of the adoption of green purchasing are environmental regulations, consumer pressures, corporate social responsibility and expected business benefits. There are four hypotheses constructed in this research. 150 electronic questionnaires were distributed via email to the unit of analysis which is the E&E companies in Malaysia. The data collected were analysed using the Statistical Package for Social Science (SPSS). Results from this study shows that environmental regulations and consumer pressures have significant impact on green purchasing. Recommendations for future research has also been included.